Local Traditions in Shaping Tolerance and Harmony Among Religious Communities: A Case Study in the Village of Sadar Kerukunan Batu Nindan - Susi, Susi; Rupiadi, Rupiadi (Jurnal Ilmiah Religiosity Entity Humanity (JIREH), 2026)
The issue of interreligious tolerance is a significant challenge in multicultural societies, where differences in beliefs can potentially lead to social friction if not managed wisely. In this context, this study aims to analyse the role of the local traditions of the Batu Nindan village community in shaping and maintaining interreligious tolerance through the perspectives of tolerance theory and conflict theory. The research used a descriptive qualitative approach with participant observation, in-depth interviews, and document study techniques, which were analysed thematically with source and method triangulation. The findings show that local traditions function as a social adhesive that encourages everyday interfaith interaction through communal practices such as customary deliberation, cultural celebrations, and cross-faith mutual aid. These traditions also facilitate intergenerational transmission of tolerance by cultivating empathy, mutual respect, and religious moderation through social customs and community-based learning. In addition, they provide a culturally legitimate mechanism for preventing and resolving social tensions through peaceful deliberation led by traditional and religious figures, grounded in principles of fairness and social justice. Local rituals and shared symbols further reinforce collective identity and social legitimacy, renewing residents’ commitment to harmony and cohesion. Theoretically, these results demonstrate that Batu Nindan traditions operate as a practical platform for enacting tolerance values and managing potential conflict, contributing to an inclusive and harmonious social order.